Serial Kasus Tatalaksana Sulit Jalan Napas pada Tumor Tiroid - Sudadi; Bayu, Timor Krisna; Widodo, Untung; Wisudarti, Calcarina Fitriani Retno; Farid, Anisa Fadhila (Jurnal Komplikasi Anestesi, 2023)
This case report studies three patients with difficult airways managed according to the American Society of Anesthesiologists (ASA) algorithm. The first case is a 46-year-old woman with bilateral SNNT who underwent a subtotal thyroidectomy without prior hyperthyroid therapy. The patient, with an ASA physical status II, was intubated using a videolaryngoscope. Postoperatively, the patient was cared for in the ward. The second case is a 58-year-old woman with a retrosternal goiter and comorbid hyperthyroidism and hypertension, who underwent a total thyroidectomy. The patient, with an ASA physical status II, was intubated while conscious. Postoperatively, the patient was admitted to the ICU. The third case is a 60-year-old woman with bilateral SNNT planned for thyroidectomy and permanent tracheostomy. The patient, with an ASA physical status III and comorbid hyperthyroidism, had failed intubation attempts with a videolaryngoscope and fiber optics. The patient could not be intubated, and the family was educated about the condition. This study demonstrates the importance of individualized management in patients with difficult airways, following ASA guidelines for optimal results.